ЦИФРОВІ ТРАНСФОРМАЦІЇ ТА АНАЛІЗ ІНСТИТУЦІЙНИХ ЗМІН В УПРАВЛІННІ ЗАКЛАДАМИ ОХОРОНИ ЗДОРОВ’Я - Валерій ГАРБУЗЮК (Herald of Khmelnytskyi National University. Economic sciences, 2026)
The article examines the specific features of healthcare system transformation under the influence of digital technologies and destabilizing factors affecting the management of healthcare institutions. The importance of digital transformation in creating a patient-centred and accessible healthcare service experience is revealed. The development of telemedicine, remote monitoring, hospital-at-home models, and home-based healthcare is characterised. The increase in the share of outpatient visits conducted through telemedicine in psychiatry, neurology, internal medicine, gastroenterology, and family medicine is analysed. The role of artificial intelligence as a key factor in the transition from reactive healthcare models to predictive, personalised, and preventive approaches is identified. The main areas of artificial intelligence application in medical imaging, diagnostics, disease prevention, personalised treatment, administrative processes, and resource management are summarised. Emphasis is placed on the dependence of the effectiveness and safety of AI solutions on the quality, standardisation, accessibility, and reliability of medical data, as well as on their validation in real clinical settings. Institutional changes in Ukraine’s healthcare system during 2019–2024 are considered, including the development of eHealth, improvements in healthcare institution management, and the transformation of hospital districts, palliative care, rehabilitation, telemedicine, and medical and social assessment. Particular attention is paid to the impact of the COVID-19 pandemic and the Russian Federation’s full-scale aggression on healthcare infrastructure, financing, service accessibility, and the organisation of medical care. The high share of direct household expenditure on healthcare is analysed. The structure of citizens’ complaints submitted to the National Health Service of Ukraine regarding violations of patients’ rights is considered. It is concluded that the combination of global digital trends and national challenges shapes a distinct trajectory for the development of Ukraine’s healthcare system, in which digital tools and artificial intelligence have both modernising and adaptive significance.